Acid-catalyzed chirality-transferring intramolecular Friedel–Crafts cyclization of α-hydroxy-α-alkenylsilanes. Issue 59 (9th July 2019) - Sakaguchi, Kazuhiko; Kubota, Shunnichi; Akagi, Wataru; Ikeda, Naoko; Higashino, Masato; Ariyoshi, Shoma; Shinada, Tetsuro; Ohfune, Yasufumi; Nishimura, Takahiro
Abstract : Acid-catalyzed intramolecular Friedel–Crafts cyclization of optically active α-hydroxy-α-alkenylsilanes possessing a benzene ring (>99% ee) with TMSOTf as a Lewis acid gave enantio-enriched tetrahydronaphthalenes (up to 98% ee). Abstract : Acid-catalyzed intramolecular Friedel–Crafts cyclization of optically active α-hydroxy-α-alkenylsilanes possessing a benzene ring (>99% ee) with TMSOTf as a Lewis acid gave enantio-enriched tetrahydronaphthalenes (up to 98% ee). The silyl group attached to the chiral carbon played a crucial role in the chirality transfer.